Ø¯ÙˆØ± Ø§Ù„Ø¨ÙŠØ¦Ø© Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ ØªÙ†Ù…ÙŠØ© Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ù…Ø¹Ù‡Ø¯ Ø¯Ø§Ø± Ø§Ù„Ø³Ù„Ø§Ù… Ø³ÙŠØºÙˆÙ† Ø¬ÙˆÙ…Ø¨Ø§Ù†Ø¬ - Wahdatussurur Assaidah; Muâ€™at; Abdul Ghofur (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2021)
The environment is one's first facility to get any language, either mother tongue or second language. Arabic as a second language (foreign) can be obtained through the Arabic environment otherwise known as the "Arab Environment". The environment is very important in achieving speaking skills. This can be obtained formally or informally at a certain level of education The focus of this research: a) Speaking skills of Students of Pondok Pesantren Darussalam Sengon Jombang, b) Arabic language environment in Pondok Pesantren Darussalam Sengon Jombang, and c) The role of the Arabic language environment in improving the speaking skills of students of Pondok Pesantren Darussalam Sengon Jombang. In this study, the researcher used the qualitative approach to study the case.. This study illustrates the role of the Arabic language environment in improving the speech skills of the students of Pondok Pesantren Darussalam Jombang, daily activities, and supporting factors for the development of Arabic. Data obtained through observation, interview and documentation. Analyze data using data reduction, data presentation, and data collection. The results of the research obtained are: a) the ability of students to speak Arabic is extraordinary and very diverse, depending on the educational background of the students themselves, b) The Arabic language environment in this cottage is categorized as an active and effective language environment because students in everyday life always speak Arabic as their mandatory language, and there are supportive activities in the development in the field of Arabic, c) The language environment in this cottage has an important role in improving the speaking skills of its students, for example new students who are not familiar with Arabic will gradually get used to it, and can eventually speak Arabic actively because it often intersects with Arabic.